EXPERIENCE OF WOMEN REGARDING THE QUALITY OF CARE DURING LABOUR AND CHILDBIRTH IN HILLY DISTRICT OF NEPAL - Gautam Bhattarai, Saraswoti Kumari; Wajih, Wahid Abdullah; Pradhan Joshi, Sarala; Prem Prasad Panta (Malaysian Journal of Public Health Medicine, 2025)
The childbirth experience is a significant event in a woman’s life and reflects the quality of maternal care. This study aimed to assess women’s experiences of care during labour and childbirth in Jumla. A facility-based, prospective, observational study was conducted among 406 pregnant women, including both low- and high-risk cases, in their third trimester, who attended antenatal clinics and were followed up in postpartum. Systematic random sampling was applied, and data were collected through face-to-face interviews using a semi-structured questionnaire based on WHO standards for maternal and newborn care. Descriptive statistics were used for analysis. Findings showed that 83.2% of women received good-quality care during labor and childbirth. Among different aspects, 93.8% received prompt service, 87.7% were satisfied with examinations, 87.4% received informed consent, 49.5% had a positive experience with a birth companion, 75.4% felt empowered, 68.7% reported privacy, 93.8% were not subjected to violence, 90.4% had good physical facilities, 88.2% received good postnatal care, and 85.2% got proper counseling and education. Nearly one-fifth of women still received poor-quality care, highlighting important gaps that require focused improvement. Limited access to birth companionship, which enhances emotional support and maternal confidence, remains a critical area for strengthening.